A short note on the noncoprime regular module problem - Ercan, G.; Güloğlu , Ş. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.5Considering a special configuration in which a finite group $A$ acts by automorphisms on а finite group $G$ and the semidirect product $GA$ acts on the vector space $V$ by linear transformations, we discuss the existence of a regular $A$-module in $V_{A}.$